2020
DOI: 10.1108/jcms-07-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of capital structure for firms in an Islamic equity index: comparing developed and developing countries

Abstract: PurposeThe paper aims to identify the differences between developed and developing country firms with respect to firm-specific and country-level determinants of their capital structure. For this purpose, all constituent firms in one of the oldest Islamic equity indices, Dow Jones Islamic Market World Index (DJIM), are considered and the Muslim-majority status of each firm's domicile country is recognized.Design/methodology/approachThe study employs Hausman–Taylor random effects regression with endogenous covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
(57 reference statements)
3
23
1
Order By: Relevance
“…In general, when viewed from the effect of GROW on STD, H4 is accepted. These results are in line with research conducted by Al-Hunnayan (2020); Czerwonka and Jaworski (2021); Kahya et al (2020). However, some researchers have found that GROW can have a negative effect ( (Alipour et al, 2015;Chandra et al, 2019;Sheikh & Qureshi, 2017), even Bolarinwa and Adegboye (2020); Dawar and M. Hull (2014) found that GROW had no significance to the debt structure.…”
Section: Variablesupporting
confidence: 88%
See 2 more Smart Citations
“…In general, when viewed from the effect of GROW on STD, H4 is accepted. These results are in line with research conducted by Al-Hunnayan (2020); Czerwonka and Jaworski (2021); Kahya et al (2020). However, some researchers have found that GROW can have a negative effect ( (Alipour et al, 2015;Chandra et al, 2019;Sheikh & Qureshi, 2017), even Bolarinwa and Adegboye (2020); Dawar and M. Hull (2014) found that GROW had no significance to the debt structure.…”
Section: Variablesupporting
confidence: 88%
“…The greater the size of the company will increase the agency cost due to the asymmetric information that arises. This result contradicts the findings of Al-Hunnayan (2020); Bukair (2019); Etudaiye-Muhtar and Abdul-Baki (2020); Guizani and Ajmi (2021); Kahya et al (2020); Khan et al (2020), stating that in Islamic banking in the Middle East and developing countries, SIZE had a positive and significant effect. In this study, the Non-debt tax shield (NDTS) had no significant effect on STD.…”
Section: Variablecontrasting
confidence: 70%
See 1 more Smart Citation
“…Researchers who raise the issue of capital structure in Islamic finance are still limited, even though this issue is very interesting to study. The Islamic financial system has its own uniqueness because it follows sharia principles, so that it is free from Maysir, Gharar and Riba (Kahya et al, 2020). This uniqueness should also create a difference between the Islamic capital structure and the conventional capital structure.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been particularly interested in the evolution of theory and the validity of contemporary finance theory. Furthermore, one of the essential aspects of corporate finance is capital structure (Kahya et al, 2020) Corporate finance and capital structure refer to the mix of debt and equity that companies employ to support their operations and development (Cheema et al, 2017). As a result, finance managers must choose the optimum financing strategy, whether debt or equity, to increase their company's performance (Daud et al, 2016).…”
Section: Introduction and Background Of Studymentioning
confidence: 99%